Grade-based similarity prevails in online course forums at scale. (March 2022) - Poquet, Oleksandra; Nguyen, Quan; Kovanovic, Vitomir; Brooks, Christopher; Dawson, Shane; Biotteau, Alexandre
Abstract: Discussion forums are the primary medium for supporting in-course student interactions in digital learning settings. Despite the significant uptake of discussion forums, questions remain as to how the tool can be used to initiate, maintain, and support interpersonal student connections. Large-scale patterns of student online interactions in forums derived from across the university are under-explored. Most studies have relied on data derived from a single course. This study presents a multi-site analysis of student interactions in online course forums at the university-level. Digital interactions of 14, 643 students were analysed across several years in three universities located in the North American, South-East Asian, and Pacific regions. Descriptive results indicate that students with similar grades tend to co-participate in learning discussions. We applied exponential random graph modelling and regression analysis to further understand this observed similarity. Results suggest that this phenomenon can be explained by social processes of selection only to a small extent, and even less so by peer influence mechanisms. The study suggests that occurrence of similarity stems from other factors, such as course and forum designs. The implications of these results raise questions regarding learning designs and the benefits linked to the formation of student connections based on grade similarity. Highlights: This study is the first large-scale multi-site analysis of university online course forums. The study describes grade-based similarity for students in online course forums at scale. At the university level, students participate online with those in the same or neighbouring academic performance-bands. Factors other than social processes appear to influence why students of similar performance co-participate online. A change of academic grade based on peer connections in the online discussion is unlikely.